2015
DOI: 10.1007/s00423-015-1305-z
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration about the aggressive surgery for resectable pancreatic cancer: a focus on real pathological portosplenomesenteric venous invasion

Abstract: Pancreatic cancer carries a high risk of recurrence even if surgical resection is technically possible. The current study suggested that portosplenomesenteric involvement and preoperative high serum CA19-9 are poor prognostic indications; however, the findings provided little insight into the role of neoadjuvant therapy in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Seven studies reported comparison of the clinicopathologic features between patients with and without histopathologic SMV/PV invasion [4, 7, 10, 13, 1820]. Pooled analysis showed that patients with SMV/PV invasion had higher rates of poor tumor differentiation ( P = 0.002), lymph node metastasis ( P < 0.001), perineural invasion ( P < 0.001), positive resection margins ( P = 0.004), and postoperative tumor recurrence ( P < 0.001) as compared with patients without SMV/PV invasion, including those who underwent pancreatectomy without SMV/PV resection (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported comparison of the clinicopathologic features between patients with and without histopathologic SMV/PV invasion [4, 7, 10, 13, 1820]. Pooled analysis showed that patients with SMV/PV invasion had higher rates of poor tumor differentiation ( P = 0.002), lymph node metastasis ( P < 0.001), perineural invasion ( P < 0.001), positive resection margins ( P = 0.004), and postoperative tumor recurrence ( P < 0.001) as compared with patients without SMV/PV invasion, including those who underwent pancreatectomy without SMV/PV resection (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Data from the last 5 years examining arterial resection for curative surgical intent for PDAC have changed compared to the past 20 years ago. Interestingly, many centers are reporting 5-year survival rates (around 20%) for patients who undergo arterial resection, which is improved compared to the previous results, reaching, in selected cases and after NAT, 53 months of median survival (Table 3) (2, 15, 24, 37, 7586).…”
Section: Pancreatectomies Associated With Artery (±Vein) Resections Amentioning
confidence: 87%
“…A multicenter study conducted in Italy found that pathological MPV invasion ( P = 0.0052) and adjuvant chemotherapy ( P = 0.0041) were significantly associated with prognosis[6]. Okabayashi et al[14] found that the incidence of postoperative peritoneal dissemination and the accumulative rate of recurrence at 2 years after surgery in the MPV+ group were higher than those in the MPV- group. Therefore, it has been proven that combined MPV resection is a safe surgical technique[11-13].…”
Section: Discussionmentioning
confidence: 99%